Intuition and Its Role in Students' Mathematical Reasoning Ability - Sri Lestari; Saiful Marom; Rochmad Rochmad (Program Studi Tadris Matematika IAIN Salatiga, 2022)
This study aims to find out more about intuition and its role in shaping students' mathematical reasoning abilities. In the discussion of the philosophy of mathematics intuition plays an important role. Intuition has been discussed by philosophers of mathematics for centuries. It is said that intuition is a provisional guess. In relation to mathematical reasoning ability, it is an indispensable ability for students because mathematical reasoning skills greatly contribute to the development of a set of 21st century skills. The method in this research is a library study approach. Researchers collect various references and sources, both international and national journals, books, and other articles related to the theme to be discussed. From the results of the discussion obtained intuition and mathematical reasoning ability are two things that complement each other in solving a mathematical problem. Intuition, which is a candidate for evidence, is then formally proven by mathematical reasoning with mathematical reasoning indicators. Intuitive processes direct the analytical process while quickly serving as a bridge in performing analytical reasoning. So if a person's intuition is good then his mathematical reasoning ability is also good. The potential of mathematical intuition in developing mathematical reasoning abilities is based on the theory that one component of intuition is reasoning